Low-Overhead Continuous Monitoring of Service Level Agreements - Okanović, Dušan; Vidaković, Milan; Konjović, Zora (International Journal of Industrial Engineering and Management, 2012)
Constant monitoring and verification of the software are required in order to assure the software meets service levels required by the service consumer are met by the service provider. We propose a new XML schema for defining service level parameters. In documents based on this schema we define parts of application to be monitored, which metric is going to be used and what are expected values. We present the DProf tool for adaptive continuous monitoring of software performance, which is based on Kieker framework. The overhead generated by this system is lower then that of the other tools or Kieker framework extensions. The system is implemented in Java, but, with minor modifications, it can be used for .NET applications. Article history: Received (22 December 2011); Revised (24 January 2012); Accepted (06 February 2012)